Discovery of New Trichophyton Members, T. persicum and T. spiraliforme spp. nov., as a Cause of Highly Inflammatory Tinea Cases in Iran and Czechia - Čmoková, Adéla; Rezaei-Matehkolaei, Ali; Kuklová, Ivana; Kolařík, Miroslav; Shamsizadeh, Forough; Ansari, Saham; Gharaghani, Maral; Miňovská, Viera; Najafzadeh, Mohammad Javad; Nouripour-Sisakht, Sadegh; Yaguchi, Takashi; Zomorodian, Kamiar; et al. (Microbiology spectrum, 2021)
Pathogens from the Trichophyton benhamiae complex are one of the most important causes of animal mycoses with significant zoonotic potential. In light of the recently revised taxonomy of this complex, we retrospectively identified 38 Trichophyton isolates that could not be resolved into any of the existing species. These strains were isolated from Iranian and Czech patients during molecular epidemiological surveys on dermatophytosis and were predominantly associated with highly inflammatory tinea corporis cases, suggesting possible zoonotic etiology. Subsequent phylogenetic (4 markers), population genetic (10 markers), and phenotypic analyses supported recognition of two novel species. The first species, Trichophyton persicum sp. nov., was identified in 36 cases of human dermatophytosis and one case of feline dermatophytosis, mainly in Southern and Western Iran. The second species, Trichophyton spiraliforme sp. nov., is only known from a single case of tinea corporis in a Czech patient who probably contracted the infection from a dog. Although the zoonotic sources of infections summarized in this study are very likely, little is known about the host spectrum of these pathogens. Awareness of these new pathogens among clinicians should refine our knowledge about their poorly explored geographic distribution. IMPORTANCE In this study, we describe two novel agents of dermatophytosis and summarize the clinical manifestation of infections. These new pathogens were discovered thanks to long-term molecular epidemiological studies conducted in Czechia and Iran. Zoonotic origins of the human infections are highly probable, but the animal hosts of these pathogens are poorly known. Further research is needed to refine our knowledge about these new dermatophytes.
Keywords: Young Adult; Cattle; Zoonoses; dermatophytosis; Male; nemoci skotu; retrospektivní studie; Child, Preschool; Iran; Cattle Diseases; Dogs; kočky; mladý dospělý; fylogeneze; mikrosatelitní repetice; Adolescent; skot; Česká republika; Child; Phylogeny; Trichophyton benhamiae complex; skin mycoses; dítě; zoonózy; Adult; Tinea; Aged; dospělí; mužské pohlaví; senioři; zoonotic infections; mladiství; Czech Republic; předškolní dítě; Microsatellite Repeats; Animals; lidé; ženské pohlaví; Trichophyton; zoophilic dermatophytes; Humans; zvířata; Dog Diseases; molecular epidemiology; nemoci psů; psi; Retrospective Studies; nemoci koček; Írán; Female; tinea; Cat Diseases; lidé středního věku; Cats; multigene phylogeny; Middle Aged